Potential Utilization of Cocoa Waste from Gunung Kidul Cocoa Fermentation Center: The Influence of NaOCl in Cellulose Extraction from Cocoa Pod Husk - Nafira Alfi Zaini Amrillah; Farrah Fadhillah Hanum; Aster Rahayu; Alliya Balqis Viratu Hapsari; Nuraini Nuraini (Agroindustrial Technology Journal, 2024)
The side of the production of the Gunung Kidul Cocoa Fermentation Center, DIY, in the form of cocoa pod husk, can cause a buildup of rubbish and become a nest for fungi that cause disease. Maximizing the use of cocoa shell waste is an effort so that people can increase the use value of waste into products that have higher economic value, one of which is extracting the cellulose. Cellulose fiber has several advantages such as good mechanical properties, low density, environmentally friendly, abundant, cheap, non-toxic, easily degraded, and included in renewable natural resources. Cellulose is obtained through an extraction process with two stages, namely alkaline delignification and bleaching. Therefore, this research aims to utilize the potential of cocoa pod husk in cellulose extraction for optimum conditions for the bleaching process with NaOCl 5%, 8%, 10% and 12% through analysis of yield, water content, ash content and FTIR characterization. Based on research that has been carried out, optimum results for cellulose are obtained through bleaching NaOCl 8% which has the best level of lightness and a yield of 52%. Chesson datta characterization also shows that cellulose NaOCl 8% NaOCl has the lowest water content and ash content, namely 1.4% and 0.8% respectively. FTIR analysis shows that the optimum results have the -OH stretching functional group as a representation of cellulose at wave numbers 3206 cm-1, 3442 cm-1 and 3600 cm-1. The presence of a peak in the wave number indicates that the bleaching process has succeeded in isolating the cellulose in the cocoa pod husk